The Danish labor market, 2000–2020 - Torben M. Andersen (IZA World of Labor, 2021)
Denmark is often termed a "flexicurity" country with lax employment protection legislation, generous unemployment insurance, and active labor market policies. This model is not a safeguard against business cycles, but has coped with the Great Recession and the Covid-19 pandemic, avoiding large increases in long-term and structural unemployment. The pandemic has had severe effects due to restrictions and lockdowns, but the recovery and re-openings in late 2020 and spring 2021 have been strong, indicating that the labor market effects are mainly temporary. Recent reforms have boosted labor supply and employment. Real wage growth has been positive and responded—with some lag—to the developments in unemployment.
Keywords: F44; L1; J1; J6; J61; 330; flexicurity; business cycles; structural policies; youth unemployment; immigration